2015
DOI: 10.1017/s1089332600002990
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Paleobotanical, Paleosol, and Stratigraphic Data to Study Critical Transitions: A Case Study From The Late Cretaceous–Paleocene Of India

Abstract: During the Cretaceous and Paleogene, the Indian subcontinent was isolated as it migrated north from the east coast of Africa to collide with Asia. As it passed over the Reunion hotspot in the late Maastrichtian–early Danian, a series of lava flows extruded, known as the Deccan Traps. Also during this interval, there was a major mass-extinction event at the Cretaceous–Paleogene boundary, punctuated by a meteorite impact at Chicxulub, Mexico. What were the biological implications of these changes in paleogeograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 103 publications
0
29
0
Order By: Relevance
“…The specimen was recovered from chert at the locality of Singpur, ca 60 km northwest of Nagpur, central India. Singpur is among numerous paleobotanical localities exposed in the Deccan Intertrappean beds of central India representing flora that existed immediately prior to and following the Cretaceous-Tertiary boundary (Prakash 1960, Smith et al 2015. The Singpur locality is likely of late Maastrichtian age based on the palynological correlation (Samant et al 2008).…”
mentioning
confidence: 99%
“…The specimen was recovered from chert at the locality of Singpur, ca 60 km northwest of Nagpur, central India. Singpur is among numerous paleobotanical localities exposed in the Deccan Intertrappean beds of central India representing flora that existed immediately prior to and following the Cretaceous-Tertiary boundary (Prakash 1960, Smith et al 2015. The Singpur locality is likely of late Maastrichtian age based on the palynological correlation (Samant et al 2008).…”
mentioning
confidence: 99%
“…These megafloral evidences (e.g., Palmoxylon woods, Brachyphyllum leaves, Viracarpon fruits, and Araucaria seeds) have been mainly recorded from the Mohgaon‐Kalan intertrappeans or adjoining sections of the Mandla sub‐province and attest presence of sub‐tropical to tropical vegetation in the region. Detailed studies on the anatomical features of the silicified woods (mainly from the Mandla sub‐province) suggest prevalence of a mesic, subtropical to tropical climate during the deposition of the DVSS in the sub‐province (Smith et al, ). These inferences were also supported subsequently by Wheeler, Srivastava, Manchester, and Baas (), who carried out a detailed examination of thin sections of >40 species of permineralized wood specimens belonging to families, viz., Anacardiaceae, Achariaceae, Lamiales (Lamiaceae), Simaroubaceae; subfamilies, viz., Planchoideae (Lecythidaceae), Leeoideae (Vitaceae), and Myrtoideae (Myrtaceae); and tribes, viz., Grewioideae, Sterculioideae (Malvaceae), and Castilleae (Moraceae).…”
Section: Palaeoecological Aspectsmentioning
confidence: 99%
“…It is pertinent to mention here that there exists a long history of research (intitiated during the early half of the 20th century) on the permineralized megafloral remains (silicified woods, chertified fruits, and flowers) from the DVSS in a palaeoecologic context (Manchester, Kapgate, & Wen, 2013 prevalence of a mesic, subtropical to tropical climate during the deposition of the DVSS in the sub-province (Smith et al, 2015).…”
Section: Freshwater-terrestrial Ecosystemmentioning
confidence: 99%
“…The Deccan Intertrappean Beds of India preserve a rich fossil record of plants which spans the Cretaceous/Paleogene boundary (Kapgate 2005, Srivastava 2012, Smith et al 2015. Determining the species composition of the floras in pre-and post-boundary localities will help us to assess plant response to local and global environmental perturbations.…”
mentioning
confidence: 99%
“…In the continuing investigation of multiple localities of the Deccan Intertrappean beds of central India (Kapgate 2005, Smith et al 2015, several plant taxa have been found to be shared among localities considered to represent the late Maastrichtian flora. These include the angiosperms Enigmocarpon (Sahni 1943), "Musa" cardiospermum (Jain 1963), Graminocarpon (Chitaley & Sheikh 1971), Indovitis (Manchester et al 2013), Pantocarpon (Kapgate et al 2007, Manchester et al in press), Sahnipushpam (revised, Kapgate et al 2011) and Viracarpon (revised, Matsunaga et al 2018).…”
mentioning
confidence: 99%